Vascular endothelial cell-surface proteoglycans - Hiss, Donavon C (Division of Medical Biochemistry and Structural Biology, 2017)
A predominant species of heparan sulfate proteoglycan that consisted of at least two subunits linked by disulfide bonding was isolated from cell layers of normal ("cobblestone") bovine vascular endothelial cells in culture. Treatment of the parent molecules with dithiothreitol caused their complete cleavage and permitted the subsequent separation of the larger and smaller subunits on Sepharose CL4B columns. Removal of dithiothreitol by dialysis resulted in the reformation of large disulfide-bonded molecules but such recombination of the subunits was prevented by prior reductive alkylation using iodoacetamide. Buoyant density gradient analysis as well as gel chromatography on Sepharose CL6B columns, following alkaline borohydride and nitrous ac i d treatment of individual carbohydrate-rich subunits, showed that the latter consisted of core proteins associated solely with heparan sulfate glycosaminoglycans. The sizes of the latter were estimated by chromatographic techniques to be approximately 50 000 and 14 000 daltons in the case of the larger and smaller subunits, respectively. This is the first description of disulfide-bonded proteoheparan sulfates in bovine aortic endothelial cells. Studies of the effects of various extracellular matrices on the proliferative behaviour of bovine aortic endothelial cells in culture revealed that extracellular matrix material from rat smooth muscle cells stimulated proliferation more than did other matrices. Bovine aortic endothelial cells also changed their morphology and cell-surface proteoglycan profiles in response to particular extracellular matrices. Enzymic modifications of matrices did not, however, cause noticeable changes in the cell surface proteoglycans synthesized by bovine aortic endothelial cells. This discrepancy suggested that the observed differences in cell-surface proteoglycan profiles cannot be ascribed to any specific single constituent of the extracellular matrix but that its overall architecture may be the sole determinant of such differences. When the turnover of endothelial cell proteoglycans was assessed, degradation of both intracellular and pericellular proteoglycans was inhibited by lysosomotropic agents. This indicated that these macromolecules may be degraded within the lysosomes; the cell layer proteoglycans are apparently internalized prior to their degradation in this location. Failure by both NH₄Cl and chloroquine completely to block the degradation of intracellular as well as pericellular proteoglycans suggested that other mechanisms of degradation also exist. The results extend biochemical data on endothelial cell surface proteoglycans.